Progress of coproporphyrin as an endogenous biomarker for transporter-mediated drug-drug interactions - Zhao, Pengfei; Hu, Yin; Hu, Xinhua; Xu, Yichao; Jiang, Bo; Lou, Honggang (Frontiers in Pharmacology, 2026)
Drug-drug interactions (DDIs) can present challenges in both the development of new drugs and clinical practice. Transporters play a pivotal role in the pharmacokinetics, safety, and efficacy of combination drug therapies. The limitations of conventional methods for evaluating transporter-mediated DDIs in vitro and in vivo have prompted the recognition of the necessity for alternative strategies. Endogenous substrates of transporters, such as coproporphyrins (CPs, including CP-I and CP-III), have emerged as promising biomarkers, particularly for organic anion transporting polypeptides (OATP1B)-mediated DDIs. This review summarizes the progress of CPs as endogenous biomarkers for transporter-mediated drug interactions. Additionally, the integration of CPs with model-based technologies is discussed to improve the quantitative prediction of OATP1B-mediated DDIs. Finally, we discuss the present challenges, including the absence of clearly defined thresholds, the effect of diseases, and the necessity of selective subtype biomarkers. Future exploration should focus on fully integrating existing evidence with models and advanced technologies, as well as subsequent pathways to gain regulatory approval. In summary, CPs are promising endogenous biomarkers for OATP1B-mediated DDIs, offering considerable potential to improve the efficiency and safety of drug development and clinical practice.